“I learned by watching”. Training Scenes for Migrant Bolivian in La Plata, Argentina - Martínez, Darío Gabriel (2021)
This article describes, from a sociocultural perspective, the training processes undergone by horticultural producers in the city of La Plata. Our purpose is to examine how horticultural knowledge and practices are transmitted in Bolivian migrant families engaged in this activity. For this, ethnographic interviews were conducted with 25 different producers who work in one of the most important horticultural areas of Argentina. From their testimonies, we observe the making complex process they have done, from a very young age, in this productive activity.